THE ADVANTAGES OF BEING A MEMBER OF THE EUROPEAN MONETARY UNION AND ITS INFLUENCE ON TRADE IN THE EUROZONE - Stanković, Milica S (International Journal of Economic Practice and Policy, 2013)
The European Monetary Union is of great importance for its member states, since being its part implies a lot of privileges. One of them is transaction costs reduction due to the elimination of currency exchange. Lower transaction costs enable easier and much more profitable trade between Member States of the European Monetary Union. The most notable achievement of the European Monetary Union is the single currency – the euro which becomes frequently used today in the international trade. A significant benefit is an elimination of foreign exchange risks since it influences reinforcement of internal market and reduces investment risks. Price transparency in trade between two Member States and within them, leads to the price homogenisation in the EU. This work examines and analyses the advantages of being the part of the European Monetary Union, with a particular attention paid to its influence on trade in the Eurozone.